Effectiveness of Group Cognitive Behavioral Therapy for Insomnia (CBT-I) in a Primary Care Setting. Issue 2 (4th March 2019) - Davidson, Judith R.; Dawson, Samantha; Krsmanovic, Adrijana
ABSTRACT: Objective/Background: Primary care is where many patients with insomnia first ask for professional help. Cognitive-behavioral therapy for insomnia (CBT-I) is the recommended treatment for chronic insomnia. Although CBT-I's efficacy is well established, its effectiveness in real-life primary care has seldom been investigated. We examined the effectiveness of CBT-I as routinely delivered in a Canadian primary care setting. Participants: The patients were 70 women and 11 men (mean age = 57.0 years, SD = 12.3); 83% had medical comorbidity. Methods: For the first 81 patients who took the six-session group program we compared initial and postprogram sleep diaries, sleep medication use, Insomnia Severity Index (ISI), the Hospital Anxiety and Depression Scale (HADS), and visits to the family physician. Results: Sleep onset latency, wake after sleep onset, total sleep time, sleep efficiency, and ISI scores improved significantly ( p < .001). Mood ratings also improved ( p < .001). Use of sleep medication decreased ( p < .001). Effect sizes were medium to large. Eighty-eight percent of patients no longer had clinically significant insomnia (ISI score ≤ 14) by the last session; 61% showed at least "moderate" improvement (ISI score reduction > 7). Wait-list data from 42 patients showed minimal sleep and mood improvements with the passage of time. Number of visits to the family physician six months postprogram decreased, although not significantly ( p = .108). Conclusions: The CBT-I program was associated with improvement on all sleep and mood measures. Effect sizes were similar to, or larger than, those found in randomized controlled trials, demonstrating the real-world effectiveness of CBT-I in an interdisciplinary primary care setting.